Histidine Alleviates Impairments Induced by Chronic Cerebral Hypoperfusion in Mice - Song, Jiangman; Yang, Lu; Nan, Di; He, Qihua; Wan, You; Guo, Huailian (Frontiers in Physiology, 2018)
Chronic cerebral hypoperfusion is one of the fundamental pathological causes of brain disease such as vascular dementia. Exploration of effective treatments for this is of great interest. Histidine has been reported to be effective in anti-apoptosis, antioxidant and against excitotoxicity. In the present study, we aim to investigate whether histidine could have a therapeutic effect on the impairments induced by chronic cerebral hypoperfusion. Cerebral hypoperfusion model was established through bilateral carotid arteries stenosis (BCAS) operation in Tie2-GFP mice. Radial arm maze and Morris water maze revealed that histidine showed potential improvement of the tendency of cognitive impairments induced by hypoperfusion. The possible mechanisms were further investigated. After administration of histidine in hypoperfusion mice, immunofluorescent BrdU staining revealed more new-born nerve cells. In vivo observation through a cranial window under two-photon laser-scanning microscopy demonstrated that the blood flow velocity in capillary was improved, the distance between the astrocytes and the penetrating artery was shortened. Histidine administration also significantly increased the protein expression level of zonula occludens protein 1, an indicator of the integrity of blood-brain barrier (BBB). These results suggest that histidine could alleviate the impairments induced by chronic cerebral hypoperfusion in mice, and this effect may be related to the neurogenesis, astrocytes and the integrity of the BBB.